2010
DOI: 10.1002/fuce.200900120
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Glycol Electrooxidation on Smooth and Nanostructured Pd Electrodes in Alkaline Media

Abstract: The electrooxidation of ethylene glycol (EG) has been studied either in situ on a smooth Pd electrode by FTIR spectroscopy or on nanostructured Pd‐based catalysts by cyclic voltammetry. The electrooxidation on the Pd electrode is dramatically influenced by the pH. Below pH 12, CO2 is formed and detected in the thin layer by FTIR, while at higher pH values glycolate, carbonate and oxalate are formed almost simultaneously at a potential of ca. 0.4 V versus RHE. Above 0.9 V glycolate is oxidised to oxalate and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 45 publications
3
65
1
Order By: Relevance
“…In fact, according to literature, adsorbed hydroxyl species are required to release the carboxylic acid upon coupling with Pd-acyl species. 30,53 −2 ) and 2.7 times higher than Pd/MWCNT-SO 3 H. The J f /J b values for the four catalysts are above 2 for EG but above 3 for the GLY. This indicates excellent tolerance of the catalysts to the presence of the carbonaceous products from alcohol oxidation.…”
Section: Spectroscopy and Microscopic Characterizationmentioning
confidence: 82%
See 2 more Smart Citations
“…In fact, according to literature, adsorbed hydroxyl species are required to release the carboxylic acid upon coupling with Pd-acyl species. 30,53 −2 ) and 2.7 times higher than Pd/MWCNT-SO 3 H. The J f /J b values for the four catalysts are above 2 for EG but above 3 for the GLY. This indicates excellent tolerance of the catalysts to the presence of the carbonaceous products from alcohol oxidation.…”
Section: Spectroscopy and Microscopic Characterizationmentioning
confidence: 82%
“…Indeed, at high potential, are formed surface palladium oxides that are inactive for the electrooxidation of alcohols. 30,52 The backward scan peak can be associated with the oxidation of freshly chemisorbed EG or GLY. In fact, previous CV studies of ethanol oxidation on Pd showed that the decrease in current at high voltages was mainly due to the formation of a PdO layer, which blocked the adsorption of the substrate.…”
Section: Spectroscopy and Microscopic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerate is further oxidized to tartronate and, by cleavage of C-C bond, into glycolate and formate. The latter species lead to carbonate and glycolate is oxidized to oxalate [25][26][27][28]. G is also oxidized directly to tartronate (path b) by chelating adsorption on catalytic surfaces.…”
Section: Other Alcoholsmentioning
confidence: 98%
“…However, the oxidation of G yields significant amounts of carbonate. Since oxalate is very slowly oxidized on Pd-based electrodes [25,26,29,30] CO 2 is prevalently a by-product of the oxidation of either glycerate or glycolate.…”
Section: Other Alcoholsmentioning
confidence: 99%